Digital Business As An Effort To Increase Income For Msmes In Border Areas - Veneranda Rini Hapsari Rini; Usman Usman; Noviyanti P; Yoseph Erbito (Jurnal Info Sains : Informatika dan Sains, 2023)
Bengkayang Regency is an area in the neighboring border region with Malaysia. Economic growth in the region is one of the keys to successful development in the region. In Bengkayang Regency, apart from farming, people who work for the government also have a profession as entrepreneurs, namely as Micro, Small and Medium Enterprises (MSMEs). These MSME businesses vary, such as culinary, services, tourism and trade. Micro business development can be carried out if it is supported by knowledge and government intervention, so that micro businesses can continue to develop. This research aims to determine the development of digital-based businesses in MSMEs to increase income in their businesses. The informants in this research are micro business actors in Bengkayang Regency. Data collection techniques use techniques through observation, interviews and documentation, data analysis techniques using data reduction, data presentation and drawing conclusions